COVID-19 Pandemic in Peru: Reflections on Its Gravity and the Nation’s Reaction - Lozano , Rafael Baldomero López (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
On the 30th of January 2020, the Director-General of the World Health Organization (WHO) declared the corona virus disease (COVID-19) outbreak as a global public health emergency of international concern, according to the International Health Regulations (2005). Against the rapidly evolving situation of the Covid-19 pandemic, many countries are facing challenges in the health sector and the economy. This essay seeks to share some reflections on the COVID-19 pandemic in Peru. The central idea of this paper argues that both the Peruvian State and society did everything they could to the best of their ability and, despite the nearly 200 thousand deaths, the greatest humanitarian catastrophe in the country’s history could have been avoided if the state-actors had (a) compare the COVID-19 epidemic with other events in our history; (b) talk about the strengths and weaknesses when handling the crisis; (c) estimate what would have happened had no action been taken.